Imaging of Anterior Nucleus of Thalamus Using 1.5T MRI for Deep Brain Stimulation Targeting in Refractory Epilepsy. Issue 8 (11th July 2016) - Jiltsova, Elena; Möttönen, Timo; Fahlström, Markus; Haapasalo, Joonas; Tähtinen, Timo; Peltola, Jukka; Öhman, Juha; Larsson, Elna‐Marie; Kiekara, Tommi; Lehtimäki, Kai
Abstract : Background: Deep brain stimulation (DBS) of the anterior nucleus of thalamus (ANT) is an evolving treatment option in refractory focal epilepsy. Due to poor visualization of ANT in traditional MRI sequences used for movement disorder surgery, targeting of ANT is mainly based on stereotactic atlas information. Sophisticated 3T MRI methods enable visualization of ANT, but 1.5T MRI is still preferred or more readily available in a large number of centers performing DBS. Objective: In the present study, we sought to determine whether ANT could be adequately visualized at 1.5T MRI pre‐ and postoperatively using imaging techniques similar to the ones visualizing ANT in 3T MRI. A total of 15 MRI examinations with short tau inversion recovery (STIR) and T1‐weighted magnetization prepared gradient echo (MPRAGE) images were performed to visualize ANT in nonepileptic subjects ( n = 2), patients with vagus nerve stimulator (VNS) ( n = 3), stereotactic MRI ( n = 3), patients with ANT‐DBS ( n = 7). Results: ANT was distinctly visualized in STIR and T1‐weighted MPRAGE images in patients without implanted stimulators, with Leksell stereotactic frame and with fully implanted VNS. Postoperative 1.5T MRI was able to demonstrate some of the anatomical landmarks around ANT enabling assessment of electrode contact locations. Conclusions: The visualization of ANT is possible in preoperative 1.5T MRI enabling direct targeting of ANT all examined situations. The use of indirect targeting and its inherent potential for lead misplacement due to anatomical variation may be avoided using these MRI methods. Furthermore, postoperative MRI with STIR and T1‐weighted MPRAGE images enable detailed postoperative assessment of contact locations.